Effects of vascular occlusion on biceps brachial hypertrophy in men in the city of Santarém-Pará (Research, Society and Development, 2022)
The goal of the research was to compare the use of vascular occlusion with low loads with conventional strengthening with high loads in the hypertrophy of the biceps brachii. The biceps brachii muscle is a fusiform shape in which its belly is thick and flattened and its ends thin, this muscle is part of the forearm and are the first to define when starting a routine of physical activities. The research, cross-sectional and epidemiological, carried out in two gyms, for its execution relied on the application of high loads with the objective of conventional strengthening and the second group composed of volunteers who used vascular occlusion with low loads, for 3 times a week, having a duration of 4 weeks for both groups and who are aged 18 to 45 years or older, who regularly train biceps brachii and who have been in the gym for at least 6 months, the main criterion being participation and application of the questionnaire. The research methodology had a quantitative approach. The acquired results were significant intragroup statistical findings and there was an increase between before and after training, in both groups. In the vascular occlusion group, the shorter the training time, the greater the gain. In conclusion, there was a greater contribution of vascular occlusion in muscle hypertrophy for the biceps brachii, although both groups have shown results, training with vascular occlusion with low loads is as effective as the traditional modality with high loads.